Boosting mineral revenues in Zambia: Policy options for a sustainable fiscal regime - Andrew Mwaba; Steve Kayizzi-Mugerwa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Zambia has changed its mineral tax regime repeatedly during the past decades in a bid to raise mineral revenue, but with only modest success. This paper looks at what the country needs to do to create a mining fiscal regime that could sustain operations, boost output, and raise revenues without eroding investment and profitability in the mines. The paper argues that enhancing local ownership of the mines will help assuage resource nationalism while stabilizing the business environment overall. Looking ahead, it will be important for Zambia to build expertise within the line ministries and the tax agency (the Zambia Revenue Authority) for analysing mineral tax and related policies, including issues of domiciliation, transfer pricing, tax loopholes, and how best to address the emerging decarbonization agenda. The creation of a dedicated unit for mining within the tax agency, preferably headed by a commissioner, could help enhance productivity.
Keywords: E62; Q33; Q38; H26; 330; fiscal regime; investment; mineral tax; resource nationalism; transfer pricing; decarbonization agenda